Urgent Care Centers, Hospital Performance and Population Health - Sonia R. Bhalotra; Letícia Nunes; Rudi Rocha (Institute of Labor Economics (IZA), 2020)
Hospitals are under increasing pressure as they bear a growing burden of chronic disease while also dealing with emergency cases that do not all require hospital care. Many countries have responded by introducing alternative facilities that provide 24/7 care for basic and medium-complexity cases. Using administrative data, we investigate impacts of the opening of these intermediate facilities (UPA) in the state of Rio de Janeiro in Brazil. We find that an UPA opening in the catchment area of a hospital reduces hospital outpatient procedures and admissions and that this is associated with improved hospital performance, indicated by a decline in inpatient mortality. This does not appear to derive from a change in the risk profile of cases going to hospital but rather from hospital resources being re-focused. In a significant departure from related research, we identify displacement by investigating population-level outcomes. Our most striking result is that a large share of the decline in hospital mortality is offset by deaths in UPAs, though there remains a net decline in deaths from cardiovascular conditions that are typically amenable to primary care.
Keywords: I11; I15; I18; 330; urgent care centers; hospital performance; displacement effects; health outcomes